The Effectiveness of Group-Based Acceptance and Commitment Therapy on Self-Worth and Resilience in Obese Women - Khatibi, Fereshteh; Khanmohammadi Otaghsara, Arsalan; Heydari, Shaban (Psychology of Woman Journal, 2025)
Objective: This study aimed to examine the effectiveness of group-based Acceptance and Commitment Therapy (ACT) on enhancing self-worth and resilience in obese women in Amol, Iran. Methods and Materials: A quasi-experimental design with pre-test, post-test, and follow-up stages was used. Fifty obese women with a BMI between 30 and 39.9 were purposefully selected and randomly assigned to an experimental group (n = 25) and a waitlist control group (n = 25). Inclusion criteria included age between 25 and 60, residence in Amol, willingness to participate, and no interfering psychological or situational conditions. The experimental group received 12 weekly sessions of group-based ACT, while the control group received no intervention during the study period. Data were collected using the Self-Worth Questionnaire (SWQ) and the Connor-Davidson Resilience Scale (CD-RISC) at three time points. Data were analyzed using ANCOVA and MANCOVA with SPSS-24. Findings: Results showed that ACT had a statistically significant effect on both self-worth (F(1, 46) = 14.31, p < .0001, η² = .222) and resilience (F(1, 46) = 8.85, p < .0001, η² = .146) at the post-test stage compared to the control group. However, at the follow-up stage, differences between the groups were no longer statistically significant for either self-worth (F(1, 46) = 2.97, p = .092) or resilience (F(1, 46) = 0.115, p = .736), indicating that the initial gains were not maintained over time without continued intervention. Conclusion: Group-based Acceptance and Commitment Therapy significantly improved self-worth and resilience in obese women in the short term, though the effects diminished at follow-up. These findings highlight the potential of ACT as an effective psychological intervention for obese women, while underscoring the importance of ongoing support to sustain therapeutic gains.